PENGAWASAN MASYARAKAT PADA PENGELOLAAN KEUANGAN DI DESA MAMUYA KECAMATAN GALELA KABUPATEN HALMAHERA UTARA - GOGASA, ISWANDI; LALOMA, ALDEN; RURU, JOORIE MARHAEN (Sam Ratulangi University, 2018)
The purpose of the study was to explain the Supervision of Society in Financial Management in Mamuya Village, Galela District, North Halmahera Regency. This study used descriptive qualitative method. Community Supervision in Financial Management was observed from two criteria namely preventive and repressive. The research informants were the village head / village government, village secretary: BPD chairperson, members (BPD), community. Data collection uses interview guidelines, documentation study observations while analysis techniques are carried out through data collection, data reduction, data presentation stages. Based on the results of data analysis concluded that Community Supervision of Financial Management in Mamuya Village, Galela Subdistrict, North Halmahera District was observed from two criteria, namely preventive and repressive, not yet maximally implemented. Based on the results of the study found that Community Supervision on Financial Management has not been maximized so that advice can be recommended: The quality of the human resources of the village head and village apparatus needs to be improved through training in village financial management. Community involvement in financial management is increased so that there are no irregularities between village and community governments, and sources of village financial revenue and other sources of income that are regulated in Government Regulation Number 113 Year 2014 concerning village financial management, and Law. No. 6 of 2014 concerning villages, be optimized.